2017
DOI: 10.4995/wrs.2017.6478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a short-term feed restriction on growth performance, blood metabolites and hepatic IGF-1 levels in growing rabbits

Abstract: A total of 144 weaned hybrid HYLA rabbits (40-day-old) were randomly divided into 4 groups, to investigate the effects of the intensity of one week's feed restriction on short-and medium-term growth performance, blood metabolites and hepatic IGF-1 in growing rabbits. Restricted groups were fed with 30% (Group L30), 50% (Group L50) 70% (Group L70) of ad libitum feeding for 1 wk and then fed ad libitum until the end of the experiment (75 d of age). The control group (Group AL) was fed ad libitum throughout the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…+10%; p < 0.05 of all tested diets) PUN levels that animals fed under ad libitum conditions [ 44 ]. Similar trends ( p = 0.051) were observed in other works [ 45 ]. In general terms, this metabolic alteration could be explained as a catabolism caused by the absence of ingestion, prior to the time of blood extraction.…”
Section: Discussionsupporting
confidence: 91%
“…+10%; p < 0.05 of all tested diets) PUN levels that animals fed under ad libitum conditions [ 44 ]. Similar trends ( p = 0.051) were observed in other works [ 45 ]. In general terms, this metabolic alteration could be explained as a catabolism caused by the absence of ingestion, prior to the time of blood extraction.…”
Section: Discussionsupporting
confidence: 91%
“…Feeding practices such as restricted feeding are known to affect physiological and productive traits in growing rabbits [18, 19, 32]. Lu et al [33] reported that, after returning to ad libitum feeding, feed-restricted animals can show compensatory growth [34, 35], increased nutrient digestibility [16, 36], and increased feed conversion rate [37]. This compensatory growth depends on the duration, level, and pattern of feed restriction [16, 17, 36, 38].…”
Section: Discussionmentioning
confidence: 99%